Peningkatan Kemampuan Penelusuran dan Pemanfaatan E-Resources Bagi Pustakawan di Pekanbaru - Hadira Latiar; Rosman H; Nining Sudiar (BIDIK: Jurnal Pengabdian kepada Masyarakat, 2021)
The information age creates abundant digital information sources (e-resources) through the internet. The abundance of digital information encourages humans to search and use it to meet information needs. However, not all information on the internet can be taken to be genuine, valid and reliable references. So, this service activity was carried out aimed at providing technical guidance to librarians in Pekanbaru. The method used in this activity is by providing technical guidance on tracking and utilizing e-resources to librarians. The result of this activity is an increase in the librarian's understanding and skills in the strategy and utilization of e-resources an average of 24.5%, as well as scientific articles that have been sent to the journal Bidik. The suggestion from the dedication is that the training participants should apply the knowledge gained from the training in each library, and it is better if similar activities should be held in the field of library science.